Enhancement of photoelectrochemical water splitting response of WO3 by Means of Bi doping - Kalanur, Shankara S.; Yoo, Il Han; Eom, Kiryung; Seo, Hyungtak (Journal of Catalysis, 2018)
Doping is a very effective strategy for tailoring the electronic band structure and improving the charge transport properties of WO3, which could in turn enhance its photoelectrochemical (PEC) activity. In this work, we report a facile hydrothermal route to synthesize Bi doped WO3 thin films on fluoride-doped tin oxide (FTO) glass substrate and investigated the insights of its band alignment. Systematic doping of Bi into WO3 was achieved during the condensation of peroxopolytungstic acid (PTA) in the course of hydrothermal synthesis. The effect of Bi doping on the morphology and crystal structure was investigated and the approximate amount of Bi incorporated into WO3 was estimated using energy dispersive spectroscopy (EDS). Results of UV–Vis spectroscopy, Mott-Schottky analysis and valence-band (VB) X-ray photoelectron spectroscopy revealed that the insertion of Bi into the lattice of WO3 changes the band gap, valence band maximum, and the conduction band minimum of WO3. PEC measurements displayed remarkable enhancement in photocurrent values from 0.401 mA cm−2 for un-doped WO3 to ∼1.511 mA cm−2 (ca. 4-fold increase) for optimized Bi doped WO3 samples at 1.23 V vs. RHE under simulated AM 1.5 G sunlight without the addition of catalysts. The results of electrochemical impedance spectroscopy confirmed that doping WO3 with Bi lead to low charge transfer resistance across the electrode/electrolyte interface and an increase in charge-carrier density. This work suggests that Bi doping has the potential to significantly improve the PEC water splitting efficiency of WO3.
Keywords: Band edge position; Bismuth doping; Charge transfer resistance; Electrode/electrolyte interfaces; Energy dispersive spectroscopies (EDS); Morphology and crystal structures; Photoelectrochemical water splitting; Tungsten oxide; Band edge position; Bismuth doping; Carrier density; Photoelectrochemical water splitting; Tungsten oxide